2007
DOI: 10.1186/1477-7827-5-32
|View full text |Cite
|
Sign up to set email alerts
|

Does measuring early basal serum follicular lutinising hormone assist in predicting In vitro fertilization (IVF)/Intracytoplasmic sperm injection (ICSI) outcome?

Abstract: Early follicular serum LH measurements in the 6 months before IVF/ICSI treatment cycle did not correlate with the clinical pregnancy or the live birth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…The observed lack of association between low baseline LH levels and poor IVF outcome is in agreement with studies consisting of patients undergoing either the long GnRH agonist suppressive (6)(7)11) or the GnRH antagonist (8) COH protocol.…”
supporting
confidence: 83%
“…The observed lack of association between low baseline LH levels and poor IVF outcome is in agreement with studies consisting of patients undergoing either the long GnRH agonist suppressive (6)(7)11) or the GnRH antagonist (8) COH protocol.…”
supporting
confidence: 83%
“…22 The basal serum LH does not predict IVF/ICSI clinical pregnancy in routine fertility and endocrinological conditions. 23 In this study it is observed that effect of ovarian aging on FORT is negligible as compared to PFC, basal E2 and FSH levels and antral follicles continue to respond to FSH irrespective of ovarian aging which is supported by other studies. 11,24 The present study reflected that high peak E2 (at the time of OI) is associated with greater number of oocytes maturity, retrieval, fertilization, cleavage and the number of top quality embryos which enhance chances of clinical pregnancy as observed in other studies 14,25 The suggested high peak E2 for improvement of oocyte and embryo quality was observed in high FORT group of our study, similar results were shown in another study.…”
Section: Discussionsupporting
confidence: 84%
“…Potential low responders were identified from either or both of the following criteria: [1] previous low ovarian response (defined by <3 oocytes retrieved) with DR and/or [2] women who required more than 300 IU/d starting dose of gonadotropin, based on the multivariate prediction model comprising of woman's age, basal serum FSH level, and body mass index (BMI) (22)(23)(24).…”
mentioning
confidence: 99%